The poetry of Abraham Valdelomar - Silva-Santisteban Ubillús, Ricardo (2017)
Abraham Valdelomar poetry is little studied in comparison to his stories. For this reason, this paper explains the importance his poetry has to guide the horizon of the Peruvian poetry. "Luna Park" and "Nocturno" are analyzed. These poems that do not invite verbal boast of modernism but with their simplicity move us by the genuine feeling they transmit. Concisely, they are poems that draw the path that Peruvian poetry should follow in the future.